HARMONY OF NATIONAL AND UNIVERSAL SPIRITUAL VALUES (American Journal of Research in Humanities and Social Sciences, 2022)
The article is devoted to the actual problems of education of the culture of interethnic relations. The harmonious combination of the universal and the national is of particular importance against the background of increasing globalization processes around the world.